2020
DOI: 10.1186/s12896-020-00645-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of three mosaic disease resistant cassava cultivars

Abstract: Background Cassava is a staple food for over 800 million people globally providing a cheap source of carbohydrate. However, the cultivation of cassava in the country is facing to viral diseases, particularly cassava mosaic disease (CMD) which can cause up to 95% yield losses. With aim to supply farmers demand for clean planting materials, there is need to accelerate the production of the elite cultivars by use of tissue culture in order to cope with the demand. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…High concentrations of NAA can disrupt the delicate balance of hormonal signaling involved in root formation, leading to a delay or inhibition of root emergence in crown flower. This follows the opinion of Sessou et al (2020), stating that increasing the concentration of NAA can inhibit root formation. In addition, according to Adugna et al (2020), different genotypes of each explant also influence the root formation process.…”
Section: Root Emergence Timesupporting
confidence: 75%
“…High concentrations of NAA can disrupt the delicate balance of hormonal signaling involved in root formation, leading to a delay or inhibition of root emergence in crown flower. This follows the opinion of Sessou et al (2020), stating that increasing the concentration of NAA can inhibit root formation. In addition, according to Adugna et al (2020), different genotypes of each explant also influence the root formation process.…”
Section: Root Emergence Timesupporting
confidence: 75%
“…Regarding plantlets rhizogenesis, a highly significant effect was observed on MS supplemented with NAA (0.5 mg/l) + ZEAT (0.5 mg/l) and NAA (0.5 mg/l) + BAP (0.5 mg/l) that highlighted the role of NAA in roots formation [15]. These results therefore indicated that each variety may require a particular combination of growth regulators.…”
Section: Discussionmentioning
confidence: 74%
“…Few years ago, cassava breeding research in Benin has leaded in the clearance of some local cultivars with important economic value [9,10]. Since the multiplication of cassava cultivars in field by cutting was limited in the numbers of planting materials, bulky, and chore intensive, research works have been started for in vitro culture of cassava [11][12][13][14][15]. Therefore, the improvement strategies for producing planting material through in vitro tissue culture remained an alternative and fast propagation method [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For now, the most common method of cassava propagation is taking stem cuttings. However, this approach is somewhat prone to introducing diseases that threaten cassava production [ 3 , 4 ]. Tissue culture technology is, therefore, increasingly seen as an effective alternative method by which to rapidly obtain a large number of virus-free plantlets [ 5 ].…”
Section: Introductionmentioning
confidence: 99%